Associations between Physical Activity, Depression, and Quality of Life in Elderly: Meta-Analysis - Fatchurrohmah Ines Prabandari; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, 2020)
Background: The aging process is associated with a greater prevalence of long-term health problems. One of them is a significant increase in problems including mental health problems in the elderly demographic. The World Health Organization (WHO) estimates that about one in every ten elderly people suffer from depress